The Hydraulic Performance Evaluation of a Compound Sharp Crested Weir with a Modified Trapezoidal–Semicircular Configuration - Bashboosh, Nabaa Noori; Hassan, Fadhel Abdulabbas; Zwain, Hanadi H. (Engineering, Technology & Applied Science Research, 2025)
In this study, experimental work was performed to represent the flow within an open channel and through a compound weir of semi-circular and trapezoidal sections for different flow conditions. This study aims to evaluate the hydraulic performance of the compound weir by finding the value of the coefficient of discharge, Cd, and deriving an equation linking the value of Cd to the rest of the hydraulic and geometric parameters governing the flow conditions. Fifteen laboratory models of a sharp-crested compound weir were tested inside a laboratory channel with dimensions of 0.3 m wide, 0.45 m high, and 15 m long. The dimensions of the compound weir opening were changed while maintaining the general shape, which consisted of a trapezoidal part with a different side slope (θ) and a semicircular part that remained constant. The effects of water depth over the crest of compound weir (h), the depth of water upstream compound weir (hu), the diameter of the semi-circular part (D), the width of the first base of the trapezoidal part (b1), the width of the second base of the trapezoidal part (b2), the perpendicular height of the trapezoidal part, and the slope of the trapezoidal side (θ) were taken into consideration in deriving a non-dimensional formula representing the relationship between these parameters and Cd. Using Excel 365 and SPSS 26 software, a non-linear relationship was derived to estimate Cd, and a good value of the coefficient of determination (R2) was achieved.